Coordinate My Care: a clinical service that coordinates care, giving patients choice and improving quality of life. Issue 4 (1st December 2012) - Smith, Clare; Hough, Libby; Cheung, Chi-Chi; Millington-Sanders, Catherine; Sutton, Eileen; Ross, Joy R; Thick, Michael; Riley, Julia
Abstract : Introduction: If palliative care is to lead the way towards a new model for integrated care, the ability to share information across the whole of health and social care is essential. Coordinate My Care (CMC) is a service dedicated to preserving dignity and autonomy at the end of life. Its care pathways enable health professionals from primary and secondary care to put the patient at the centre of health care delivery. This service is underpinned by an electronic solution. The CMC record can be accessed 24/7 by all health and social care professionals who have a legitimate relationship with the patient. Patients and methods: The record displays diagnosis, prognosis, advanced care plan, resuscitation status and patients wishes for end of life care patients across London. This article is a review of CMC use and outcomes from August 2010- March 2012. Results: 1087 CMC patient records were analysed. The primary diagnosis was non-cancer in 52.3%, cancer in 46.3% and unknown in 1.4%, 42% of all patients were cared for by generalist only and had no specialist palliative care involvement. At the time of analysis 207 had died. Actual place of death was home 38.6%, care/nursing home 16.4%, hospice 12.1% and 30% in hospital. This equates to 55% of patients dying in their usual place of residence and reflects that 70% died outside of hospital. Conclusion: The CMC service has a well defined pathway underpinned by an electronic solution. It has been shown to change culture and deliver fully integrated, personalised end of life care. A pan-London CMC roll out will take place over the next 12 months.